Estrategias metodológicas y su incidencia en el aprendizaje de los niños y niñas del primer año de educación básica de la escuela fiscal mixta “Riobamba” de la parroquia de Turubamba en la ciudad de Quito. Periodo lectivo 2013-2014 - Torres Obando, Rocío Margarita (2015)
This research work, called "METHODOLOGICAL STRATEGIES AND THEIR IMPACT ON THE LEARNING OF CHILDREN FIRST YEAR OF BASIC EDUCATION SCHOOL TAX MIXED “Riobamba" TURUBAMBA PARISH OF QUITO, LECTIVO PERIOD 2013-2014", is structured and developed in accordance with Regulations Graduation force at the National University of Loja. As formulated the overall objective: To demonstrate that the use of methodological strategies in learning is important for the formal educational process and the identity of the children of first year of Basic Education of the Joint Fiscal Riobamba Parish School Turubamba in Canton Quito from Pichincha Province in the 2014-2015 school year. The methods used were: the scientific method, inductive, analytic-synthetic and statistical. The technique applied was: the document review to collect information and elaboration of the theoretical framework. Teachers and students of the First Year Basic Education Mixed Fiscal School "Riobamba" Two research instruments were applied. Addressing a single survey to identify the pedagogical theories used by teachers and learning styles test applied to students, to diagnose the methodological strategies to be implemented by teachers in the social context of the group of students who enroll in the school of study. Part of the results achieved with the interview educators determined that 33% know that the implementation of educational theories, this interacts with other disciplines such as psychology, sociology and biology, an update of knowledge being necessary. As for the results of the test applied to infants have the following result 32% of children in the first year of basic education are hearing what it means to think and remember sequentially and orderly manner, 31% are visuals that are linking learning with images, 28% are kinesthetic need to associate content with bodily sensations or movement activities, 9% corresponds to children who for some reason was not justified or unjustified attended school.